Closed Casket : New Hercule Poirot Mysteries #2 - Hannah, Sophie, 1971-; Christie, Agatha, 1890-1976 (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2016)
Lady Athelinda Playford announces her decision to cut her children out of her will and leave her fortune to an invalid with just weeks to live, a declaration Hercule Poirot senses was made to provoke a murder.
"Agatha Christie"--Cover.
Keywords: Poirot, Hercule -- (Fictitious character) -- Fiction; Poirot, Hercule -- (Fictitious character) -- Fiction; Private investigators -- Belgium -- Fiction; Women authors -- Fiction; Disinheritance -- Fiction; Nineteen twenties -- Fiction; Detectives -- Belgium -- Fiction; Women authors -- Fiction; Inheritance and succession -- Fiction; Nineteen twenties -- Fiction; Historical fiction; Mystery fiction